Simultaneous MRI of lung structure and perfusion in a single breathhold. Issue 1 (20th December 2013) - Bell, Laura C.; Johnson, Kevin M.; Fain, Sean B.; Wentland, Andrew; Drees, Randi; Johnson, Rebecca A.; Bauman, Grzegorz; Francois, Christopher J.; Nagle, Scott K.
<x xml:space="preserve">Abstract</x> Purpose To develop and demonstrate a breathheld 3D radial ultrashort echo time (UTE) acquisition to visualize co‐registered lung perfusion and vascular structure. Materials and Methods Nine healthy dogs were scanned twice at 3 Tesla (T). Contrast‐enhanced pulmonary perfusion scans were acquired with a temporally interleaved three‐dimensional (3D) radial UTE (TE = 0.08 ms) sequence in a breathhold (1 s time frames over a 33 s breathhold). The 3D breathheld volume was reconstructed into time‐resolved perfusion datasets, and a composite vascular structure dataset. For structural comparison, a 5 min respiratory‐gated 3D radial UTE scan was acquired. Data were analyzed by quantitative metrics and radiologist scoring. Results Appropriate time‐course of contrast was seen in all subjects. Right ventricle to aorta transit times were 7.4 ± 2.0 s. Relative lung enhancement was a factor of 8.4 ± 1.5. Radiologist scoring showed similarly excellent visualization of the pulmonary arteries to the subsegmental level in breathheld (94% of cases) and respiratory‐gated (100% of cases) acquisitions (P = 0.33) despite the aggressive under sampling in the breathheld scan. Similarly, differentiation of lung tissue and airways was achieved by both acquisition methods. Conclusion A time‐resolved 3D radial UTE sequence for simultaneous imaging of pulmonary perfusion and co‐registered vascular structure is feasible. J. Magn. Reson. Imaging 2015;41:52–59. © 2013 Wiley Periodicals, Inc.